2022
DOI: 10.3389/fmicb.2022.918120
|View full text |Cite
|
Sign up to set email alerts
|

A Large Silicon Pool in Small Picophytoplankton

Abstract: Marine picophytoplankton (<2 μm) play a key role in supporting food web and energy flow in the ocean, and are major contributors to the global marine carbon (C) cycle. In recent years, picophytoplankton have been found to have significant silica (Si) accumulation, a finding which provides a new sight into the interaction of marine C and Si cycles and questions the overwhelming role of large diatoms (>2 μm) in the Si cycle. As picophytoplankton have high cell abundance and wide distribution in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Cyanobacteria are believed to have emerged during the Neoarchean era, approximately 2.7 billion years ago (Lee, 2018) . It was reported that Si in the Synechococcus was a common phenomenon (Hildebrand et al, 1997) due to its connection with photosynthetic performance, growth rate (Wei and Sun, 2022) , and elemental composition (Geider and La Roche, 2002) . Six clones of Synechococcus experiment recently noticed a significant amount of silicon with growth rate unaffected by silicic acid concentrations between 1 and 120 μM suggesting Synechococcus lacks an obligate need for silicon.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cyanobacteria are believed to have emerged during the Neoarchean era, approximately 2.7 billion years ago (Lee, 2018) . It was reported that Si in the Synechococcus was a common phenomenon (Hildebrand et al, 1997) due to its connection with photosynthetic performance, growth rate (Wei and Sun, 2022) , and elemental composition (Geider and La Roche, 2002) . Six clones of Synechococcus experiment recently noticed a significant amount of silicon with growth rate unaffected by silicic acid concentrations between 1 and 120 μM suggesting Synechococcus lacks an obligate need for silicon.…”
Section: Resultsmentioning
confidence: 99%
“…Diatoms have been thought to dominate the marine silicon cycle (Nelson et al, 1995) , until a recent report suggested the biogenic silica (bSi) pool in the ocean may not entirely originate from diatoms and some associated with Synechococcus (Wei and Sun, 2022) . For example, Synechococcus makes up 20% of the particulate bSi in the euphotic zone in the Sargasso Sea, while in the equatorial Pacific Ocean, their contribution sometimes outweighed that of diatoms (Baines et al, 2012) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Small-sized phytoplankton also play a vital role in the carbon pool. While larger-sized phytoplankton are often assumed to be the primary contributors to carbon export, recent studies have highlighted the importance of small-sized phytoplankton in this process (Stukel and Landry, 2010;Shiozaki et al, 2019;Irion et al, 2021;Wei and Sun, 2022). Overall, understanding the implications of phytoplankton size structure is critical for predicting the response of marine ecosystems to environmental change.…”
Section: Introductionmentioning
confidence: 99%
“…Averaging field and model estimates, indicate a marine gross bSi production at 255 (±52) Tmol silicon yr −1 , of which up to 7.9% is potentially attributed to picocyanobacteria (Tréguer et al, 2021 ). A recent study calculated that picophytoplankton (<2–3 μm in diameter), including picocyanobacteria and picoeukaryotes, contribute to bSi standing stocks and production, as well as overall flux, in much more significant proportions (Wei & Sun, 2022 ). Estimates include a bSi production rate of 32–80% of 240 Tmol Si yr −1 , and responsibility for approximately 55% of global annual ocean Si flux.…”
Section: Introductionmentioning
confidence: 99%